Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4315/0362-028x.jfp-19-103
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Independent Evaluation of Bacterial Contamination Patterns on Pig Carcasses at a Commercial Slaughter Facility

Abstract: Traditionally, the microbiological status of meat is determined by culture-based techniques, although many bacteria are not able to grow on conventional media. The aim of this study was to obtain quantitative data on total bacterial cell equivalents, as well as taxa-specific abundances, on carcass surfaces during pig slaughter using quantitative real-time PCR. We evaluated microbial contamination patterns of total bacteria, Campylobacter, Escherichia coli, Lactobacillus group, Listeria monocytogenes, Salmonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, season is an important contributing factor of contamination in swine raising environments (Kumari et al, 2016) and its effect should be addressed over a longer period of time. Carcass (Dc and Cc; Figure 2) and drain samples (Dev and Dcu; Figure 3) had similar numbers of TAM and EB compared to the range reported in the literature (Spescha et al, 2006;Gill and Badoni, 2010;Zwirzitz et al, 2020), whereas Cev, Gev and Ccu samples (Figure 3) were lower (Warriner et al, 2002;Bridier et al, 2019;Zwirzitz et al, 2020). Total aerobic mesophilic, Enterobacteriaceae and coliform counts increased on the processing equipment over time (Warriner et al, 2002).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, season is an important contributing factor of contamination in swine raising environments (Kumari et al, 2016) and its effect should be addressed over a longer period of time. Carcass (Dc and Cc; Figure 2) and drain samples (Dev and Dcu; Figure 3) had similar numbers of TAM and EB compared to the range reported in the literature (Spescha et al, 2006;Gill and Badoni, 2010;Zwirzitz et al, 2020), whereas Cev, Gev and Ccu samples (Figure 3) were lower (Warriner et al, 2002;Bridier et al, 2019;Zwirzitz et al, 2020). Total aerobic mesophilic, Enterobacteriaceae and coliform counts increased on the processing equipment over time (Warriner et al, 2002).…”
Section: Discussionsupporting
confidence: 56%
“…Several 16S rRNA amplicon sequencing studies have focused on key areas of the swine value chain. The microbial ecosystem found in the air of the housing building (Nehme et al, 2008;Kumari et al, 2016;Kraemer et al, 2019;Yan et al, 2021), the swine gut Kim and Isaacson, 2015;Zhao et al, 2015;Holman et al, 2017;Crespo-Piazuelo et al, 2018;Quan et al, 2018;Xiao et al, 2018;Adhikari et al, 2019;Mark Welch et al, 2019;Vigors et al, 2020), the respiratory tract, mouth and saliva (Wang et al, 2018;Huang et al, 2019;Mou et al, 2019;Murase et al, 2019), the meat plant environment (Bridier et al, 2019;Zwirzitz et al, 2020) and the carcass (Mann et al, 2016;Zwirzitz et al, 2019;Zwirzitz et al, 2020) have been examined. Swine gut microbiota is by far the most studied of these environments, enough so that the concept of a "core" microbiota (bacteria present in over 90% of samples) was put forward by Holman et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sampling area was 100 cm 2 at the back of the carcasses. The back was chosen based on the results of a preliminary test already conducted prior the start of this study, which showed that samples taken from the back harbor similar levels of relevant microorganisms compared to samples taken from the belly or the musculature along the cutting area 53 . In total, 84 swabs were taken from carcass surfaces at different processing positions.…”
Section: Facility Structure and Samplingmentioning
confidence: 99%
“…The 16S rRNA gene was amplified by qPCR to enumerate total bacterial cell equivalents (BCE) as previously described (Supplementary Table 5 53,54 ). All qPCR samples and standards were run in duplicates and negative controls were included in each run (Mx3000P qPCR thermocycler, analyzed with MxPro v.4.10 (Stratagene, San Diego, USA)).…”
Section: Dna-extraction Qpcr and 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…The sampling area was 100 cm 2 at the back of the carcasses. The back was chosen based on the results of a preliminary test already conducted prior the start of this study, which showed that samples taken from the back harbour similar levels of relevant microorganisms compared to samples taken from the belly or the musculature along the cutting area (Zwirzitz et al 2019). In total, 84 swabs were taken from carcass surfaces at different processing positions.…”
Section: Facility Structure and Samplingmentioning
confidence: 99%